Skateboarding: Legendary tricks - Badillo, S.; Werner, D. (Tracks Publishing, 2008)
A comprehensive guidebook that details dozens of spectacular skateboarding stunts, this resource combines invaluable technical information with insightful historical perspectives. Each trick is captured in action sequence and captioned so that aspiring riders can learn how each trick is performed. A history of the tricks, featuring their legendary inventors, is also included. This blend of background and how-to ensures that riders not only learn the tricks but also gain respect for the legends that made skateboarding the worldwide passion it is today. https://books.google.de/books?id=yUVEHSJrQI4C&printsec=frontcover&hl=de&source=gbs_ViewAPI&redir_esc=y#v=onepage&q&f=false